Transformation of education under conditions of digital society development: European experience and prospects for Ukraine - Strutynska Oksana (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського, 2020)
The paper deals with analysis, generalisation and systematisation of the European experience in the field of digital transformation of education. Nowadays, when a digital society is being built, digital transformation is becoming the basis for the world economic development. This leads to a rapid change in the professions being in demand in the employment market and, consequently, the professional requirements for the qualification framework, competences in particular. Thus, educational activities require updating the content and methods of teaching, finding innovative forms of learning, expanding the access to educational resources, implementing learning opportunities without restrictions on the bases of space and time, introducing new approaches to the organisation of educational services in general. The purpose of this study is to analyse and systematise the European experience in the field of the digital transformation of education, outlining some ways to use it for transforming the education in Ukraine. The main research methods used are as follows: a systematic analysis of regulatory, scientific, and methodological sources on the digital transformation of education in European countries, the study of the methodological tools to support teachers in the development of a digital society. For the digital transformation of education, it is necessary to take a number of important steps which include: the development of normative initiatives by the state to ensure the regulatory framework enabling the transformation of education; the modernisation of educational systems, the updating of the content of school and university education; training and retraining of teachers, taking into consideration the increasing proficiency level of their digital skills and competences. The paper presents in detail how these steps are implemented in the EU. Based on the analysed sources, we can come to these conclusions: in Europe, the conditions facilitating an increase in pedagogues’ proficiency in terms of digital competences have been created; the tools aimed at supporting their activities have been developed, which contributes to the digital transformation of education in general. Ukraine has also recognised the digital transformation as a priority policy for the development of the digital economy and the emergence of a digital society as a whole. To ensure a quality educational process, the modern education system of Ukraine needs changes. The digitalisation of all levels of education, and, in the future, their digital transformation appear to be important steps in this respect.